Efecto de la aplicación de fertilizantes edáficos en fase reproductiva, en el rendimiento de dos variedades de café (Coffea arabica L) en la Finca Agro Loja, parroquia Malacatos - Poma Medina, Richard Stalin (2024)
Due to its economic, social and environmental benefits for farmers, coffee production is one of the most important agricultural crops in Ecuador, involving some 50,000 families, the majority of which are small farmers using agroforestry production systems. However, the management of the coffee plantations is deficient, especially in relation to the application of fertilizers, which influences the yield, which is generally low (5 qq/ha). In the present research the effect of edaphic fertilization during the reproductive stage was evaluated in two varieties of coffee Borboun Sidra and Typica Mejorada in Malacatos, canton Loja. Four treatments were applied (Grosso, Chemical Fertilization and Grosso + Chemical Fertilization, Control without fertilization) and the following variables were measured: number of branches, number of flowers, equatorial diameter, polar diameter, production yield in kg/ha and quality in dry matter, ash and protein. In the results, no significant differences were found between the interaction of variety and fertilization in the variables of number of branches, polar and equatorial diameter, dry matter, protein and ash, except for the number of flowers in which treatment three presents a significant difference in the two varieties with an average of 480 flowers while the other treatments have an average value of 380 flowers. In the case of production yield in kg/ha, treatment 3 (Chemical Fertilization + Grosso) stood out, in which the Bourbon Sidra variety obtained 9 999 kg/ha and the Improved Typica 7 999 kg/ha, 2 kg/ha, with respect to treatment Tes (control) which presented the lowest values 4 332.9 kg/ha and 4 899.51 kg/ha in the Bourbon Sidra and Improved Typica varieties respectively and in the variable of kg/plant it is observed that there are significant differences, having the highest production values also in Treatment 3 (Chemical Fertilization + Grosso), with a value of 2.4 kg in the Improved Typica variety and a value of 3.0 kg in the Bourbon Sidra variety.